Assessing mobility and balance in Autosomal Recessive Spastic Ataxia of Charlevoix-Saguenay population: Validity and reliability of four outcome measures - Lessard, Isabelle; Brais, Bernard; Côté, Isabelle; Lavoie, Caroline; Synofzik, Matthis; Mathieu, Jean; Gagnon, Cynthia (Journal of the neurological sciences, 2018)
To assess the construct validity of the 10-Meter Walk Test (10mWT), Six-Minute Walk Test (6MWT), Berg Balance Scale (BERG), and Timed Up and Go (TUG) in adults with Autosomal Recessive Spastic Ataxia of Charlevoix-Saguenay (ARSACS), in addition to the interrater reliability of the 10mWT and 6MWT. Reliability was determined using the intraclass correlation coefficient (ICC). Validity was determined first by correlating the 10mWT, 6MWT, BERG, and TUG with participant's age, lower limb coordination, and disease severity, and then by assessing their capacity to distinguish between participants based on sex and disease stages. Interrater reliability of the 10mWT at both comfortable and maximum speed as well as the 6MWT is excellent (ICC = 0.97–0.99). Construct validity of the four tests was confirmed, as showed by the high correlations with age, lower limb coordination, and overall disease severity (ρ = 0.64–0.97). The four tests assessed for their metrological properties in this study showed to be valid instruments to use in the ARSACS population. The 10mWT and 6MWT are also highly reliable. BERG and TUG reliability will need to be assess in a future study. •The 6MWT and 10mWT have an excellent interrater reliability (ICC >0.90).•Construct validity of the 6MWT, 10mWT, BERG, and TUG was excellent.•Change higher than 0.07 m/s is required to conclude a real change in the 10mWT-comf.•Change higher than 0.11 m/s is required to conclude a real change in the 10mWT-max.•Change higher than 50 m is required to conclude a real change in the 6MWT.